Nutrition and Lifestyle of Generation Z: Emerging Concerns for Sustainable Development Goals (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
As the first generation to fully develop in a digital environment, Generation Z is a crucial group for the future of sustainable development and public health. Emerging data shows a contradictory growth in poor diet quality, sedentary habits, and interrupted daily routines among this generation, despite increased exposure to nutrition information and sustainability rhetoric. The Sustainable Development Goals (SDGs), specifically SDG 2 (Zero Hunger), SDG 3 (Good Health and Well-Being), and SDG 12 (Responsible Consumption and Production), are examined in this narrative review, which synthesizes empirical literature published between 2015 and 2024. According to the review, the twin burden of malnutrition and early onset of non-communicable diseases is caused by an increasing reliance on ultra-processed foods, a decline in nutritional diversity, insufficient physical activity, and inconsistent sleep patterns. This report outlines important policy gaps and stresses the need for integrated, youth-focused nutrition and lifestyle interventions to advance the 2030 Sustainable Development Agenda by directly connecting behavioral patterns with quantifiable SDG indicators.